2013
DOI: 10.14430/arctic4308
|View full text |Cite
|
Sign up to set email alerts
|

Kuujjua River Arctic Char: Monitoring Stock Trends Using Catches from an Under-Ice Subsistence Fishery, Victoria Island, Northwest Territories, Canada, 1991 – 2009

Abstract: A standardized, harvest-based monitoring program was conducted during the main under-ice subsistence fishery for Arctic char (Salvelinus alpinus) of the Kuujjua River for 18 winter fishing seasons between 1991 and 2009. The program was a response to the concern of Ulukhaktok residents that Arctic char were becoming fewer in number and smaller in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…In the western Arctic, anadromous Arctic char of the Kuujjua River stock have been the subject of a long-term (1992-present), harvest-based monitoring study at Tatik Lake, Victoria Island, NT (Harwood et al, 2013). Anadromous Arctic char migrate to the ocean in summer, where they access rich marine resources for 2-3 months (Dempson and Kristofferson, 1987), building condition before migrating upstream to lakes for overwintering (Johnson, 1980;Boivin and Power, 1990;Gyselman, 1994).…”
Section: Arctic Charmentioning
confidence: 99%
See 3 more Smart Citations
“…In the western Arctic, anadromous Arctic char of the Kuujjua River stock have been the subject of a long-term (1992-present), harvest-based monitoring study at Tatik Lake, Victoria Island, NT (Harwood et al, 2013). Anadromous Arctic char migrate to the ocean in summer, where they access rich marine resources for 2-3 months (Dempson and Kristofferson, 1987), building condition before migrating upstream to lakes for overwintering (Johnson, 1980;Boivin and Power, 1990;Gyselman, 1994).…”
Section: Arctic Charmentioning
confidence: 99%
“…Anadromous Arctic char migrate to the ocean in summer, where they access rich marine resources for 2-3 months (Dempson and Kristofferson, 1987), building condition before migrating upstream to lakes for overwintering (Johnson, 1980;Boivin and Power, 1990;Gyselman, 1994). With two decades of fall sampling conducted at the same location and time of year, soon after the fish returned from summer feeding, annual measures of char condition reflect the annual quality/quantity of marine prey available in nearshore waters of the eastern Amundsen Gulf (Harwood et al, 2013). Harwood et al (2013) reported that mean annual condition indices of the char were variable among the years of study, with annual condition indices being significantly correlated with timing of sea ice retreat in spring (Fig.…”
Section: Arctic Charmentioning
confidence: 99%
See 2 more Smart Citations
“…The Inuvialuit of Paulatuk, a community of 314 (Northwest Territories Bureau of Statistics, 2013) located approximately 14 km west of the Hornaday River, have harvested char from this system for subsistence since the community was first settled in the early 1940s. The Hornaday is the largest river draining into Darnley Bay, and it supports the largest stock of Arctic char in the area, with the next large stock located 300 km to the east on Victoria Island (Harwood et al, 2013). A test fishery at the Brock River, the other main river draining into Darnley Bay (Fig.…”
Section: Introductionmentioning
confidence: 99%